Customer engagement and relationships in multi-actor service ecosystems - Sharma, Piyush; Jain, Kokil; Kingshott, Russel; Ueno, Akiko (Elsevier, 2020)
With the growing realization that most service ecosystems consist of interactions among multiple participants, including customers, employees, and others, there are increasing calls for research on the interdependent nature of customer engagements and relationships in multi-actor service ecosystems. This special issue addresses these calls with 22 articles (including three invited articles), classified along five distinct groups, including a) Co-creation, collaboration and socialization among actors, b) Actors’ (dis)engagement, c) role of the ‘other’ actors, d) dark side of multi-actor service ecosystems, and e) emerging trends – digital technologies and others. This editorial begins by reviewing the multi-actor service ecosystems literature to identify some important research gaps. Next, it briefly describes the 22 articles included in this special issue arranged along the above five themes and their major findings. Finally, the guest editors discuss the implications of these findings and some useful directions for future research in this area of growing importance.